A Study on Bipedal and Mobile Robot Behavior Through Modeling and Simulation - Nirmala, Nirmala; Tanaya, Prianggada Indra; Sinaga, Maralo (CommIT (Communication and Information Technology) Journal, 2015)
The purpose of this work is to study and analyze mobile robot behavior. In performing this, a framework is adopted and developed for mobile and bipedal robot. The robots are design, build, and run as proceed from the development of mechanical structure, electronics and control integration, and control software application. The behavior of those robots are difficult to be observed and analyzed qualitatively. To evaluate the design and behavior quality, modeling and simulation of robot structure and its task capability is performed. The stepwise procedure to robot behavior study is explained. Behavior cases study are experimented to bipedal robots, transporter robot and Autonomous Guided Vehicle (AGV) developed at our institution. The experimentation are conducted on those robots by adjusting their dynamic properties and/or surrounding environment. Validation is performed by comparing the simulation result and the real robot execution. The simulation gives a more idealistic behavior execution rather than realistic one. Adjustments are performed to fine tuning simulation's parameters to provide a more realistic performance.